Schooling and resistance to schooling in Betsiamites: a case study in a Canadian Amerindian rural reserve - Vien, Charles (Institute of Education, University of London, 1998)
Traditionally, the vast majority of Canadian Amerindians have largely remained undereducated and such is the case in Betsiamites. This 2,500 people community is the largest of the nine Montagnais reserves which are located in Eastern Québec. There has been an improvement in the overall completion rates at the elementary and secondary levels between 1970 and 1985, following the transfer of all the responsibilities for reserve schools from the federal Government to the Amerindian communities. But progress had come to a halt by the end of the 1980s and most secondary school or university Amerindian students still drop out today. By focusing on the reserve of Betsiamites, this thesis attempts to provide explanations for this situation and to suggest ways to improve the effectiveness of Amerindian education. The thesis is divided into seven chapters, including the introduction and the conclusion. In the second chapter, the assumptions underlying this thesis, the data-gathering and analysis methods and the ethical problems linked to the situation of the current researcher as former teacher and current principal of the secondary school under investigation are discussed. In the third chapter, it is argued that the 1969-1972 political battle which allowed the Amerindians to govern their education systems has overshadowed some basic and essential issues regarding quality education and is partly responsible for the lack of improvement since the mid 1980s. In the fourth chapter, the historical process which led to the creation of the reserve of Betiamites and to the generalized dependency on welfare is presented. The fifth chapter analyses the daily life of the local secondary school, from its management to the motivation of students. The sixth chapter discusses the links between the local political, economic and social life and local schooling and suggests ways of alleviating widespread educational underachievement in rural reserves. This thesis argues that despite an adverse socio-economic environment, Canadian Amerindian ...